Sustainable Fiscal Policy in a Federal System: Switzerland as an Example - Lars P. Feld; Gebhard Kirchgassner (Center for Research in Economics, Management and the Arts (CREMA), 2004)
How a sustainable fiscal policy can be performed in a federal system is not only a Swiss prob-lem but is also discussed in other federal countries like Germany and Austria, and in the European Union. Contrary to most other countries, the Swiss fiscal system is characterised by an extensive fiscal federalism with high fiscal autonomy at all governmental levels, by direct popular rights which include fiscal referenda at the cantonal and local levels, and by particular constitutional and/or statutory fiscal restraints in order to prevent excessive public debt. In this paper, the effects of these constitutional clauses on public finances are investigated. Using a panel of the 26 Swiss cantons from 1980 to 1998, we provide evidence that direct democ-racy leads to significantly lower expenditure and revenue. The fiscal constraint, on the other hand, significantly reduces budget deficits. Total, cantonal as well as local expenditure and revenue are the lower the higher the share of local expenditure is.
Keywords: D78; 330; Direct Democracy; Referenda; Initiatives